How can a spiritual pedagogy in religious education contribute to children’s spiritual growth? - Rodriguez, Mira Cataya (International journal of children's spirituality, 2025)
This paper explores how a spiritual pedagogy in religious education (RE) can contribute to children’s spiritual development to a larger extent than it currently does in the UK and in Norway. Contemporary RE focuses largely on knowledge transmission, but it could be reimagined to empower students to transform their lives by nurturing their spirituality. The paper starts by defining spirituality as a relational experience involving one’s connection with oneself, others, the natural world, and potentially the transcendent. This definition serves as a conceptual framing for the rest of the discussion, clarifying how spirituality is understood and how RE can nurture it. The paper then discusses Biesta’s pedagogical concept of subjectification, which opens up a space in RE to focus more on experiential and relational dimensions and individual empowerment. Empirically, I discuss the opportunities provided by Norwegian and British RE curricula.